COMPARATIVE ASSESSMENT OF KNOWLEDGE OF CERVICAL CANCER SCREENING PRACTICES AMONG HIV-INFECTED AND UNINFECTED WOMEN ATTENDING TERTIARY HOSPITAL IN JOS, PLATEAU STATE, NIGERIA. - Kefas, Ibrahim Bakshak; Isiko, Isaac; Okoro, Lenz Nwachinemere; Isa, Haroun; Bulus, Naya Gadzama; Asingwire, Jackson Micheal; Richman, Fortune Sunday; Kefas, Ibrahim Jane; Ahgu, Ovye (Student's Journal of Health Research Africa, 2024)
Introduction Cervical cancer is caused by human papillomavirus that affects cervical cells. It is one of the leading causes of cancer-related death in Africa. Owing to the increasing rate of cervical cancer, there is a need to evaluate the knowledge of cervical cancer screening practices among women to minimize its occurrence and progression in at-risk individuals. This study aimed to assess the knowledge of cervical cancer among HIV-infected and HIV-uninfected women attending accessing care in a tertiary hospital in Jos, Plateau State. Methods The study was a comparative cross-sectional study, conducted at BHUTH among HIV-infected and HIV-uninfected women. A structured interviewer-administered questionnaire was used to collect data which was analyzed using SPSS version 23. Results Among the respondents, 50 (40.3%) and 55 (44.4%) of the HIV-infected and HIV-uninfected women had good knowledge of cervical screening practices. Among the HIV-infected women, those with tertiary education had 8 odds (AOR=8.233, 95%CI: 2.41–28.1, p=0.001) of having good knowledge of cervical screening practices compared to those without education. Married participants and those who had 2 or more sexual partners had 0.06 odds (AOR=0.056, 95%CI: 0.01–0.35, p=0.002) and 0.2 odds (AOR=0.236, 95%CI: 0.07–0.80, p=0.02) respectively of having good knowledge of cervical screening practices compared to those who were single with 1 sexual partner respectively. Among the HIV-uninfected women, those who were non-Plateau indigenes had 2.9 odds (AOR=2.921, 95%CI: 1.25 – 6.83, p=0.013) of having good knowledge of cervical screening practices compared to those who were Plateau indigenes. Conclusion The knowledge of cancer screening practices was poor among the study participants. Therefore, the government should ensure that awareness of cervical cancer among women is improved through the dissemination of accurate information and include cervical cancer vaccinations in the national immunization program.